Triticale - Eudes, François; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Triticale crop species have received substantial research support since the mid-20th century, making it a commercial success in many countries  in diverse value propositions. No recent book, however, captures the recent advances and technological progress made over the past two decades. This book reviews and collates the latest knowledge of triticale plant biology and agronomy, while considering the contribution of biotechnology enablers such as molecular markers, doubled haploid technology, and genetic engineering in breeding for traits important for crop production, feed, food and industrial end-uses. Triticale fit for these end-uses, covered in individual chapters, demonstrates the great potential of this still young cereal crop.
Part 1. Plant Biology and Breeding -- Triticale Biology and Biosafety -- Triticale Breeding--Progress and Prospect -- The Development of Hybrid Triticale -- Part 2. Biotic and Abiotic Stress Tolerances -- Triticale Abiotic Stresses – An Overview -- Biotic Stresses – Known and Novel Foes -- Part 3. Genomics and Biotechnology Enablers -- Doubled Haploids in Triticale -- Characterization of the Genomes and the Transcriptome of Triticale -- Genetic Engineering and Precision Editing of Triticale Genomes -- Part 4. Market and Potential for Novel Uses of Triticale Crop -- Triticale: Grain for Feed and Energy -- Triticale as a Forage -- Triticale for Food – The Quality Driver -- Biomaterial Value Proposition of Triticale.
Keywords: Plant genetics; Plant breeding; Plant Genetics and Genomics; Plant Breeding/Biotechnology.